Fiscal Crisis and World Order. - Converse, Raymond W. (Algora Publishing, 2011)
The crisis facing the United States is both economic and political, and its effects are felt both at home and abroad. The author presents a detailed look at how the present world order is or could be affected by a total global economic collapse. He asks whether a world governance system is feasible and desirable, and explores what forms such a system might take, depending upon whether such players as China, the Russian Federation and the Islamic nations continue to make economic progress or suffer setbacks.